Evaluation of Different Genotypes at Codons 11, 72 and 248 of p53 Gene in Samples of Endometriosis - Hajar Dahim (Anatomical Sciences Journal, 2014)
Introduction: Endometriosis is a prevalent gynecological disorder among women which is diagnosed by the growth of endometrial tissue outside of uterus and is mainly accompanied by severe pelvic pain and infertility. P53 also known as cellular tumor antigen P53 inside codons 11, 72 and 248 are contained with single nucleotide changes in which tends to be nearly rampant.This will probably be increasing the chances of endometriosis infection to some great extent. Our aim was to evaluate the connection between endometriosis and polymorphism inside the codons 11, 72 and 248 of P53 gene. Methods: In this study, single nucleotide changes in codons 11, 72 and 284 of TP53 gene among 44 persons infected with endometriosis and the same studying population for noninfected group have been examined. After primer design and amplification of polymorphic sequences by PCR, the polymorphisms of related codons have been evaluated by the digestion method (RFLP). Results: In this study on the codon 72, there were seen differences in the distribution of genotype frequencies of normal polymorphic subjects and control subjects with endometriosis. At codons 11 and 248, there were observed no significant correlations between polymorphic and normal genotypes of endometriosis and non-endometriosis groups. Conclusion: According to the results, we can say that probably polymorphism